2017
DOI: 10.1016/j.renene.2016.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic thermal simulation of horizontal ground heat exchangers for renewable heating and ventilation of buildings

Abstract: Gan, Guohui (2016) Dynamic thermal simulation of horizontal ground heat exchangers for renewable heating and ventilation of buildings. Renewable Energy, 103 . pp. 361-371. ISSN 1879-0682 Access from the University of Nottingham repository: http://eprints.nottingham.ac.uk/38978/1/AcceptedManuscript.pdf Copyright and reuse:The Nottingham ePrints service makes this work by researchers of the University of Nottingham available open access under the following conditions. This article is made available under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Moreover, the dynamic thermal simulation of horizontally coupled earth‐liquid heat exchanger for a ground source heat pump and earth‐air heat exchanger for building ventilation was carried out in Ref . Therefore, an increase by 10 and 12% in the heat transfer through a plastic earth‐liquid heat exchanger was detected, and the earth‐liquid heat exchanger was found to be more efficient than an earth‐air heat exchanger.…”
Section: Interaction Of Building Simulation With Other Thermal‐energymentioning
confidence: 99%
“…Moreover, the dynamic thermal simulation of horizontally coupled earth‐liquid heat exchanger for a ground source heat pump and earth‐air heat exchanger for building ventilation was carried out in Ref . Therefore, an increase by 10 and 12% in the heat transfer through a plastic earth‐liquid heat exchanger was detected, and the earth‐liquid heat exchanger was found to be more efficient than an earth‐air heat exchanger.…”
Section: Interaction Of Building Simulation With Other Thermal‐energymentioning
confidence: 99%
“…Existing HGHX models are often created using FEM software and applying constant boundary conditions or calculating only short time periods as in [2], [3], [4]. In [5], a self-developed three-dimensional model is used, taking into account moisture transport and latent heat. The impact of soil moisture content and fluid flow rate on the heat extraction rate is presented.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of a numerical solution of transient transport phenomena is influenced not only by the model equations and the solution method but also by the initial conditions for soil temperature and moisture in shallow ground [23,26]. Kopecky [27] showed that the initial soil temperature was one of the most important parameters that would influence the total heat exchange through a horizontal heat exchanger for a given period.…”
Section: Introductionmentioning
confidence: 99%